Characterization of Campylobacter Jejuni Samples Coming Form Poultry Meat and Feces [Caracterización de Cepas de Campylobacter Jejuni Obtenidas Desde Carne de Pollo y Heces de Aves de Corral de la Zona Central de Chile] - Martinez-Fernandez, C; Garcia-Mena, V (Sociedad Medica de Santiago, 2017)
Background: Campylobacter jejuni is one of the main causal agents of food borne diseases. Infections with this pathogen are mainly caused by chicken meat consumption. Aim: To characterize antibiotic resistance and virulence factors in C. jejuni strains obtained from chicken meat and poultry feces in Central Chile. Material and Methods: The presence of C. jejuni in 30 meat and 40 feces samples from poultry was studied. From these samples, we obtained 40 strains which were characterized at the molecular level for the presence of 16 genes involved in virulence using PCR. In parallel, antibiotic resistance for ciprofloxacin, nalidixic acid, tetracycline, erythromycin, azithromycin, chloramphenicol y ampicillin was analyzed. Results: Twenty and 63% of feces and chicken meat samples were positive for C. jejuni, respectively. Moreover, a high percentage of strains showed antibiotic resistance, where 27% of strains were resistant to all tested antibiotics, except for azithromycin. Finally, 10% of the strains coming from feces contained 14 out of 16 virulence genes evaluated. Only 23% of the strains did not contain any of these genes. Conclusions: A high percentage of feces and chicken meat samples are contaminated with C. jejuni. Moreover, these strains show a high genetic and phenotypic diversity represented by their antibiotic resistance profiles and the presence of virulence factors. © 2017, Sociedad Medica de Santiago. All rights reserved.
Keywords: Anti-Bacterial Agents; Campylobacter jejuni; Poultry; Poultry Products